Time dependent vehicle routing problem with fuzzy traveling times under different traffic conditions - Demirel, Tufan; Demirel, Nihan Cetin (WORLD SCIENTIFIC PUBL CO PTE LTD, 2006)
Time dependent vehicle routing problem is a vehicle routing problem in which travel costs along the network are dependent upon the time of day during which travel is to be carried out. Most of the models for vehicle routing reported in the literature assume constant and deterministic travel times. This paper describes a route construction method for time dependent vehicle routing problem with fuzzy traveling times according to different traffic conditions.
Keywords: Computer Science